Ellagic Acid and Its Microbial Metabolite Urolithin a Alleviate Diet-induced Insulin Resistance in Mice (OR24-03-19). (13th June 2019) - Yang, Jieping; Guo, Yuanqian; Henning, Susanne; Chan, Brenda; Long, Jianfeng; Zhong, Jin; Acin-Perez, Rebeca; Petcherski, Anton; Shirihai, Orian; Heber, David; Li, Zhaoping
Abstract: Objectives: Pomegranates have high levels of ellagitannins (ETs) and ellagic acid (EA). ETs and EA are converted to urolithins (U) by gut microbiota in the GI tract. Both are absorbed systemically. We aimed at evaluating the metabolic effects of EA and its microbial metabolite UA in mice with diet-induced insulin resistance (IR). Methods: Male DBA2J mice were fed a Western diet (42% energy from fat, 32% from sucrose, 0.2% cholesterol) for 8 weeks to induce IR. After IR was confirmed the WD was supplemented with 0.1% EA, UA, or EA and UA combined (EAUA) for another 8 weeks. At the end of the intervention body composition, intraperitoneal insulin and glucose tolerance test (IPITT and IPGTT), serum and tissue (liver, adipose and skeletal muscle (SM)) lipids, inflammatory, metabolic and mitochondrial markers were determined. Results: Compared to WD control, blood glucose and free fatty acids were significantly decreased with EA, UA and EAUA, and IR and triglycerides were improved by EAUA only. Hepatic lipid content, histology markers of hepatic steatosis, as well as inflammatory markers (TNFα, MCP1 and IL6) in blood and all three tissues were not changed by the intervention. We observed differential regulation of genes related to mitochondrial function but not mitochondrial DNA content by EA, UA and EAUA in liver and SM. Markers of mitochondrial fusion ( Mfn2 ) and mitophagy (Parkin and Pink ) were increased by UA and EAUA compared with IR mice. In addition, primary hepatocytes from IR mice had significant higher proton leak, basal and ATP-linked oxygen consumption rates than healthy control mice. EA and EAUA but not UA reduced the proton leak in hepatocytes from IR mice. Conclusions: Dietary EA and UA differentially improved the glucose control and modified markers of mitochondrial function in liver and SM of mice with diet induced IR. Future studies are needed to understand how EA/UA mediated changes of mitochondrial function contribute to the improvement of IR. Funding Sources: Center for Human Nutrition, Department of Medicine, David Geffen School of Medicine, University of California, Los Angeles.